Dominica : First Review Under the Stand-By Arrangement and Requests for Extension of the Arrangement and for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2003)
A 12-month Stand-By Arrangement was approved to help Dominica deal with external shocks, rising public debt, and a prolonged economic downturn. Discussions focused on the appropriate mix between adjustment and financing. The authorities will also continue to strengthen the public sector investment program (PSIP) and the social safety net. Dominica's debt dynamics present an important challenge that will require continued fiscal efforts and exceptional financial support. In light of the proposed strengthened program and decisive ownership, the IMF staff recommends completion of the first review and extension of the arrangement.